2012
DOI: 10.1103/physrevd.85.065006
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of an ideal relativistic quantum fluid: A perturbative study

Abstract: We show that a quantized ideal fluid will generally exhibit a small but non-zero viscosity due to the backreaction of quantum soundwaves on the background. We use an effective field theory expansion to estimate this viscosity to first order in perturbation theory. We discuss our results, and whether this estimate can be used to obtain a more model-independent estimate of the "quantum bound" on the viscosity of physical systemsComment: Accepted for publication, Phys.Rev.D. Discussion slightly clarified and ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…[126] has recently found that this relation remains valid in a SYM plasma even when the leading order finite t'Hooft coupling corrections are taken into account. 33 The transport coefficients in the theory [127] are known analytically and, even though their numerical values are different than the ones found in this paper (their theory is different than ours), qualitatively they possess the same features found here -ξ5, ξ6 have the same signal as ours and would also display a peak where c…”
Section: Jhep02(2015)051supporting
confidence: 50%
See 1 more Smart Citation
“…[126] has recently found that this relation remains valid in a SYM plasma even when the leading order finite t'Hooft coupling corrections are taken into account. 33 The transport coefficients in the theory [127] are known analytically and, even though their numerical values are different than the ones found in this paper (their theory is different than ours), qualitatively they possess the same features found here -ξ5, ξ6 have the same signal as ours and would also display a peak where c…”
Section: Jhep02(2015)051supporting
confidence: 50%
“…where D = u µ ∇ µ is the comoving derivative, ∇ α ⊥ = ∆ αβ ∇ β is the derivative transverse to the flow, θ = ∇ µ u µ is the scalar expansion rate, and σ µν = 2∆ αβ µν ∇ α u β is the shear 3 For recent discussions including attempts to formulate dissipative hydrodynamics in terms of an effective action see, for instance, [33][34][35]. 4 Note we use the Landau frame, i.e., uµT µν = −ε u ν [21].…”
Section: Jhep02(2015)051mentioning
confidence: 99%
“…Recent investigations include [22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][49][50][51]. We will discuss connections to these earlier works along the way.…”
Section: Jhep09(2017)095mentioning
confidence: 99%
“…Where T 0 is a microscopic scale whose necessity is clear since ∂φ I is dimensionless. The role of this microscopic scale , (which also absorbs a microscopic degeneracy, such as N 2 c in gauge theories) is extensively discussed in [19,23] and will be discussed later in this work.…”
Section: A Review Of Ideal Hydrodynamicsmentioning
confidence: 99%